Images of the Feast in Antioch: Reflections about Dionysus’ Mosaics in Domestic Settings = Immagini della festa ad Antiochia : Riflessioni sui mosaici di Dioniso in contesti domestici - Silva, Gilvan Ventura da (Mythos, 2021)
In the Roman Empire, Antioch, the metropolis of Syria Coele, stood out as a vibrant cultural centre and stage of many artistic, sports and religious events, including its own Olympic Games. The Kalends of January, the Calliopea and the Maiuma were special highlights, not to mention the Christian and Jewish festivals. Antioch was filled with celebrations. The key attribute of the Antiochean people was precisely its festive ethos and fondness for singing, dancing and displays of joy and cheerfulness, both in public and domestic sites. The city was considered to be under the direct influence of Dionysus, whose cult was one of the most ancient and noteworthy religious institutions in the city. This paper analyses some mosaics depicting Dionysus in domestic settings at Antioch and its environs, especially in its connection with the symposion.